Diversity in E. coli (p)ppGpp Levels and Its Consequences - Spira, Beny; Ospino, Katia (Frontiers in Microbiology, 2020)
ppGpp is at the core of global bacterial regulation as it controls growth, the most important aspect of life. It would therefore be expected that at least across a species the intrinsic (basal) levels of ppGpp would be reasonably constant. On the other hand, the historical contingency driven by the selective pressures on bacterial lineages vary widely resulting in broad genetic polymorphism. Given that ppGpp controls the expression of many genes including those involved in bacterial response to environmental challenges, it is not surprising that the intrinsic levels of ppGpp would also vary considerably. In fact, null mutations or less severe genetic polymorphisms in genes associated with ppGpp synthesis and hydrolysis are not uncommon. Such variation can be observed in laboratory strains, in natural isolates as well as in evolution experiments. High ppGpp levels result in high resistance against environmental stresses and low growth rates. Other aspects such as virulence and antimicrobial resistance are also influenced by the intrinsic levels of ppGpp. A case in point is the production of Shiga toxin by certain E. coli strains which is inversely correlated to ppGpp basal level. Conversely, ppGpp concentration is positively correlated to increased resistance to different antibiotics such as β-lactams, vancomycin and others. Here we review the variations in intrinsic ppGpp levels and its consequences across the species E. coli.